Marketing Training Strategy for Employees of Rajawali Peanut Bread Factory in the Post-Pandemic Era in Tebing Tinggi City - Siregar, Wina Hanna; Nainggolan, Elizon (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
In the era of globalization, marketing strategy is a crucial factor for companies to survive and compete, especially in the culinary industry, such as Rajawali Peanut Bread Factory in Tebing Tinggi City. The COVID-19 pandemic has had a significant impact on this sector, necessitating the adaptation of more effective marketing strategies, including employee training in product marketing. This study aims to analyze the marketing training strategy for employees of Rajawali Peanut Bread Factory in the post-pandemic period, in order to enhance their skills and competitiveness in product marketing. This research uses a descriptive qualitative approach conducted at the Rajawali Peanut Bread Factory. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and verification. The results of the study show that the marketing training strategy is carried out through the on-the-job training method, where employees are directly guided by senior staff in marketing products. Employees are also trained to utilize social media and direct promotions to consumers. This training has proven effective in improving employees' marketing capabilities and expanding the market reach of peanut bread products.